IMPLEMENTASI KURIKULUM RELAKSASI DALAM PEMBELAJARAN MASA PANDEMI COVID-19 KOMPETENSI KEAHLIAN TKRO DI SMK N 2 YOGYAKARTA - Alif Alif Riyadi; Kir Haryana (Jurnal Pendidikan Vokasi Otomotif, 2022)
AbstractThe study aims to describe the implementation of a relaxing curriculum during the covid-19 in the competence expertise learning process at 10th grade techinical automotive Yogyakarta’s Vocational High School (SMK N 2 Yogyakarta) which included the formulating aspects of the relaxation curriculum, stake holder’s involvement, management performance’s of the learning process, obstacles during the implementation of the relaxation curriculum and follow-up of the learning curriculum used. This is a kind of descriptive research. The research subject is teachers, students of the competition for 10th-grade technical automotive engineering, and several of stakes holder (head of technical automotive light vehicle, school committee, industry, parents of students, school supervisor and covid-19 cluster head) who have a direct interest in the implementation of learning at SMK N 2 Yogyakarta. Data of this research was collected by questionnaires, interviews, documentation, and observation. Data was analyzed by descriptive statistics. The data of the research were analyzed by using descriptive statistical techniques that focused on the central tendency of the data. Studies indicate that the general conclusion of the implementation on the relaxation curriculum to studies held by SMKN 2 Yogyakarta was carried out in good. Keyword: implementation of relaxing curriculum, planning, management implementation, evaluation and follow-up about curriculum which used.